Antiinflammatory Therapy in Clinical Care: The CANTOS Trial and Beyond - Aday, Aaron W.; Ridker, Paul M. (Frontiers in Cardiovascular Medicine, 2018)
Inflammation is a critical pathway in the pathogenesis of atherosclerosis. Previous studies have shown that plasma levels of high-sensitivity C-reactive protein (hsCRP), a marker of inflammation, are associated with cardiovascular disease independent of traditional risk factors. Randomized trial data have also shown that statins reduce not only hsCRP but also cardiovascular event rates independent of their effect on low-density lipoprotein cholesterol (LDL-C) level. More recently, the CANTOS trial showed that directly reducing inflammation with canakinumab, an interleukin (IL)-1β neutralizing monoclonal antibody, could also reduce cardiovascular event rates. These mark the first phase 3 trial results validating inflammation as a viable target for preventing cardiovascular disease. In this review, we recap the role of inflammation in cardiovascular disease and highlight previous trial data showing its modulation with statins and other agents. We also detail the CANTOS trial results and discuss its implications for clinicians as well as future directions for anti-inflammatory therapy in the prevention of cardiovascular disease.